Generalized Phase Sensitivity of Directional Bond Breaking in the Laser-Molecule Interaction - Kangaparambil, Sarayoo; Hanus, Vaclav; Dorner-Kirchner, Martin; He, Peilun; Larimian, Seyedreza; Paulus, Gerhard G.; Baltuska, Andrius; Xie, Xinhua; Yamanouchi, Kaoru; He, Feng; Lotstedt, Erik; Kitzler-Zeiler, Markus (Physical Review Letters, 2020)
We establish a generalized picture of the phase sensitivity of laser-induced directional bond breaking using the H2 molecule as the example. We show that the well-known proton ejection anisotropy measured with few-cycle pulses as a function of their carrier-envelope phases arises as an amplitude modulation of an intrinsic anisotropy that is sensitive to the laser phase at the ionization time and determined by the molecule's electronic structure. Our work furthermore reveals a strong electron-proton correlation that may open up a new approach to experimentally accessing the laser-sub-cycle intramolecular electron dynamics also in larger molecules.
CRIS-Team Scopus Importer:2023-04-20